1996
DOI: 10.1152/ajpendo.1996.270.2.e336
|View full text |Cite
|
Sign up to set email alerts
|

Postmarathon paradox: insulin resistance in the face of glycogen depletion

Abstract: Acute physical exercise enhances insulin sensitivity in healthy subjects. We examined the effect of a 42-km marathon run on insulin sensitivity and lipid oxidation in 19 male runners. In the morning after the marathon run, basal serum free fatty acid concentration was 2.2-fold higher, muscle glycogen content 37% lower (P < 0.01), glycogen synthase fractional activity 56% greater (P < 0.01), and glucose oxidation reduced by 43% (P < 0.01), whereas lipid oxidation was increased by 55% (P < 0.02) compared with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 25 publications
5
56
1
Order By: Relevance
“…None of these findings were present following either the control (no exercise) or concentric exercise interventions. These results indicate that resting muscle glucose uptake is decreased following EIMD, and have been subsequently confirmed by a number of studies [10,16] .…”
Section: Glucose Uptake and Insulin Sensitivitysupporting
confidence: 74%
See 4 more Smart Citations
“…None of these findings were present following either the control (no exercise) or concentric exercise interventions. These results indicate that resting muscle glucose uptake is decreased following EIMD, and have been subsequently confirmed by a number of studies [10,16] .…”
Section: Glucose Uptake and Insulin Sensitivitysupporting
confidence: 74%
“…This initial disruption is followed by degeneration during which the damaged myofibrillar proteins are acted on by proteases. A number of studies have reported the infiltration of immune cells within 2 to 3 days following injury [14,17] , but other researchers have failed to show an immune response [2,10,20] . Regeneration follows with satellite cells becoming centrally located and replacing the damaged myofibrils.…”
Section: Physiological Changes Resulting From Exercise Induced Musclementioning
confidence: 99%
See 3 more Smart Citations